Teacher Educators and Teacher Education Reform: Individual Commitments, Institutional Realities - Cole, Ardra (Canadian Journal of Education/Revue canadienne de l'éducation, 1999)
I conducted a three-year study of pre-tenure professors of teacher education directly and indirectly involved in the reform of teacher education in Canada to gain a better under- standing of the changes in which pre-tenure teacher education faculty are engaged and of the personal and contextual influences that facilitate and constrain their efforts to do things differently. The research approach was broadly qualitative; more specifically, I conducted my research from a life-history perspective, which situates individuals’ accounts of experience within a broader personal, historical, social, political, cultural, and/or institutional context. In this article I provide an overview of the types of reform characterizing teacher educators’ work and explore some obstacles to this work, highlight- ing the intersection between individuals’ commitments to reform and institutional realities that often militate against or obstruct these efforts. L’auteure présente une étude de trois ans portant sur des professeurs en formation à l’en- seignement, en voie d’acquérir leur permanence et participant directement et indirectement à la réforme de la formation à l’enseignement au Canada. L’étude visait à mieux cerner la nature des changements mis en œuvre par ces professeurs ainsi que les influences personnelles et contextuelles favorisant ou non les efforts en vue de faire les choses autrement. Il s’agissait d’une étude qualitative, faisant appel à une approche biographique situant les comptes rendus des expériences des personnes dans un contexte personnel, historique, social, politique, culturel ou institutionnel. Dans cet article, l’auteure fait un survol de la nature des réformes caractérisant le travail des responsables de la formation à l’enseignement et explore quelques obstacles à ces efforts. Ce faisant, elle met en lumière le lien qui existe entre l’engagement personnel vis-à-vis des réformes et les réalités institutionnelles qui souvent font obstacle à ces efforts.